Pengaruh Penerapan Sistem Informasi Akuntansi dan Sistem Pengendalian Internal terhadap Kinerja Karyawan pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Sumatera Barat - Zulvia, Dewi; Sababalat, Riva (ARZUSIN, 2025)
Employee performance in public sector organizations is strongly influenced by the effectiveness of accounting information systems and internal control systems. However, there remains a gap in understanding the simultaneous contribution of these two systems to employee performance in local government institutions. This study aims to analyze the impact of accounting information system implementation and internal control systems on employee performance at the Regional Financial and Asset Management Agency of West Sumatra Province. A quantitative approach was used, employing a survey method with questionnaires distributed to employees selected through convenience sampling. The research instruments were tested for validity and reliability before being analyzed using multiple linear regression with the help of SPSS software. The results show that the accounting information system has a positive and significant effect on employee performance, indicating that an efficient system can improve productivity and work accuracy. Conversely, the internal control system shows a negative but significant effect on employee performance, suggesting that overly bureaucratic implementation can reduce flexibility and hinder work initiative. The conclusion of this study highlights the importance of optimizing accounting information systems to support work efficiency and the need to evaluate the design and application of internal control systems to ensure they align with the goal of enhancing employee performance in public organizations.